Corona Discharge – A Fully Coupled Numerical Approach Verified and Validated - Rubinetti, D; Weiss, D; Egli, W (The International Journal of Multiphysics, 2017)
Corona discharge denotes the effect where an electrically non-conducting fluid is ionized under the influence of strong electrical fields in proximity of an emitting electrode. This technology is used in industry for a broad range of applications, e.g. the deposition of airborne particles. The electrodynamic nature of Corona discharge is often coupled with other physical phenomena, making it a key element of multiphysical problems. In order to accurately describe and set-up a model for Corona discharge processes a guideline is presented here. It can be implemented into codes which allow the user-input of custom partial differential equations. The governing equations of the approach developed are based on Maxwell’s equations. The delicate part of calculating in an efficient way the electrical field distortion due to space charges is implemented by a Lagrange Multiplier, which allows the integrated identification of the unknown initial space charge density on the electrode. By means of a simplified test-case the results have been analytically verified. Additionally, the results of the modelling approach presented have been compared to experimental data available in literature, showing a good agreement.